Coordination Bonds and Diels–Alder Bonds Dual Crosslinked Polymer Networks of Self‐healing Polyurethane. Issue 22 (8th October 2019) - Lin, Changhong; Sheng, Dekun; Liu, Xiangdong; Xu, Shaobin; Ji, Fance; Dong, Li; Zhou, Yan; Yang, Yuming
ABSTRACT: A dual crosslinked self‐healing polyurethane was prepared with robust mechanical properties through the dynamic reversible pyridine‐Fe 3+ coordination bonds and Diels–Alder (DA) covalent bonds dual crosslinking strategy. Moreover, the mechanical properties and self‐healing ability of polyurethane can be tuned readily by different ratio of the coordination bonds and DA bonds. Under external load, the coordination bonds serve as sacrificial bonds are broken to dissipate energy, the DA bonds can keep the shape of sample. With the coordination bonds participation, the damaged samples can be healed under moderate heating treatment or with the aid of FeCl3 solution. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 2228–2234 Abstract : A dual crosslinked self‐healing polyurethane was prepared with robust mechanical properties through the dynamic reversible pyridine‐Fe 3+ coordination bonds and Diels‐Alder (DA) covalent bonds. The system can be healed through heat treatment or solution assistant, respectively .